Weber-Christian Panniculitis With Immune Complex Glomerulonephritis - Vassall, John H. (1985)
The etiology of Weber-Christian panniculitis is unknown. A case is presented in which an association is found between immune complex glomerulonephritis and a relapse of Weber-Christian panniculitis. This case adds to the literature, implicating immune system dysfunction in the pathophysiology of this disease.